Carbohydrate compounds as green corrosion inhibitors: electrochemical, XPS, DFT and molecular dynamics simulation studies. Issue 111 (18th November 2016) - Yadav, M.; Sarkar, T. K.; Obot, I. B.
Abstract : Corrosion inhibition effect of 5, 6-bis(2-(1 H -benzo[ d ]imidazol-2-yl)hydrazono)hexane-1, 2, 3, 4-tetraol (BIHT) and 5, 6-bis(2-(1-methyl-1 H -imidazol-2-yl)hydrazono)hexane-1, 2, 3, 4-tetraol (MIHT) on N80 steel in 15% HCl was measured by electrochemical method. Abstract : Corrosion inhibition and adsorption characteristics of synthesized carbohydrate compounds, namely, 5, 6-bis(2-(1 H -benzo[ d ]imidazol-2-yl)hydrazono)hexane-1, 2, 3, 4-tetraol (BIHT) and 5, 6-bis(2-(1-methyl-1 H -imidazol-2-yl)hydrazono)hexane-1, 2, 3, 4-tetraol (MIHT) on oil-field N80 steel in 15% HCl were measured by mass loss, polarization, EIS and PZC procedures. The compounds BIHT and MIHT are efficient corrosion inhibitors and they adsorb on the steel surface following the Langmuir adsorption isotherm. SEM, EDX, AFM and XPS were used for characterizing the surface of the steel samples after exposing them to 15% HCl without and with BIHT and MIHT. DFT and molecular dynamics simulation (MDS) were applied for theoretical studies.